Legitimacy in European nature conservation policy : case studies in multilevel governance - Keulartz, Jozef (Springer, 2017)
This volume focuses on the issue of legitimacy in the context of European nature conservation policy. It provides insights in the way in which democratic legitimacy is being ‘produced’ at different levels of governance. Building forth upon recent developments in democracy theory that have identified multiple forms of legitimacy, the volume observes a EU-wide shift from output legitimacy to input and throughput legitimacy. Top down policy making is increasingly meeting